The effect of special exercises for reactive speed) SAQ ( in developing some physical and skilled abilities of young football players - Ali Majeed Zayer, Mohammed (International Journal of Psychosocial Rehabilitation, 2020)
The football game is one of collective games that have evolved dramatically in the last period and this development was imposed on football players, particularly young people perform physical and skill duties and major tactical and seeks instructors to find the best ways to raise the possibilities , as it was one of these methods are exercises Alsakao where This method has proven its effectiveness , as the importance of the research is evidenced by experimenting with a sports training that is not used in the country, and that this training method will be highlighted through knowing the effect of using special exercises for interactive velocity (SAQ In developing some abilities and skills of young football players . The problem lies in the players’ lack of speed of movement and skillful performance during the competition and this is due to the lack of use of exercises that require a high level of reactive speed SAQ) With the skillful performance during the training units, so the researcher decided to use this training method in order to know the extent of benefit, the study aimed to prepare special exercises through interactive speed) SAQ) In the development of some physical and skill capabilities, as well as to recognize these exercises influence in the research sample development, chose the researcher demo b approach the style of the two groups Almtkavitin (experimental and control), select the research community my players Baghdad governorate for young people, such as the players in the youth club air force research sample totaling (20) The deliberate method was chosen, and the researcher conducted two exploratory experiments (exercises and testing), and the scientific foundations were applied to the test, exercises were applied to the research sample for a period of (10) weeks at a rate of (3) units per week with a total of (30) training units . After collecting data and treating them statistically, the researcher concluded that the exercises of saku are of great importance in developing the physical and skill abilities of the research sample in this study.